Water column physico-chemical profiles of lakes and fiords along the northern coastline of Ellesmere Island (Ward Hunt Island observatory) - Vincent, Warwick; Sarrazin, Denis; Hamilton, Andrew; Mueller, Derek; Antoniades, Dermot; Veillette, Julie; Copland, Luke; Lionard, Marie; Charvet, Sophie; Bourget, Sébastien (Canadian Cryospheric Information Network, 2011)
This dataset includes physico-chemical profiling records from lakes and fiords along the northern coastline of Ellesmere Island. Measured parameters (conductivity, temperature, salinity, total dissolved solids, pH, oxidation reduction potential, turbidity, dissolved oxygen) varied according to the instruments used (mainly RBR XR-420-CTD, RBR XR-620-CTD, Hydrolab Surveyor 3 and Hydrolab DS5X). This dataset spans from 1954 until 2012. Data prior to 1999 is from historical reports and published data. The most recent data was collected by the research program NEIGE. Data was collected when it was logistically possible to get to the study sites during summer. : Purpose: Long-term monitoring wthin the program NEIGE of the water column properties of Lake A, Lake B, Lake C1, Lake C2, Lake C3, Ward Hunt Lake, Ayles Fiord, Disraeli Fiord, Markham Fiord, M'Clintock Inlet, Milne Fiord, Petersen Bay, Phillips Inlet, Serson Bay and Taconite Inlet. : Summary: Not Applicable